2013
DOI: 10.3126/saarctb.v9i2.7972
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Reagarding HIV/AIDS Among Pregnant Females Attending Antenatal Clinic at Khyber Teaching Hospital Peshawar, Pakistan

Abstract: Introduction: Globally, around 34 million people are living with HIV in 2010, and 35% of the pregnant  women are tested for HIV in the low and middle income countries. HIV infection in pregnancy has  become a complication of pregnancy in some developing countries. This has major implications for  the management of pregnancy and birth. With an estimated one and a half million HIV-positive women  becoming pregnant each year, almost 600,000 children will be infected by mother-to-child transmission  annually. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…In a similar study conducted at Peshawar, only 41% knew that avoiding unsafe sex would lead to prevention of AIDS. [11] In our present study, 46(30.7%) of the respondents said that HIV was curable, and 91(60.7%) didn't know if HIV was curable. This is slightly different to the study conducted by Kumar C et al, where (42.6%) had misconception that HIV/AIDS can be cured by using medicine.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In a similar study conducted at Peshawar, only 41% knew that avoiding unsafe sex would lead to prevention of AIDS. [11] In our present study, 46(30.7%) of the respondents said that HIV was curable, and 91(60.7%) didn't know if HIV was curable. This is slightly different to the study conducted by Kumar C et al, where (42.6%) had misconception that HIV/AIDS can be cured by using medicine.…”
Section: Discussioncontrasting
confidence: 47%
“…[10] It has been observed that most of the women in the community do not have complete and correct information about HIV and it's prevention. [11] The Prevention of Parent To Child Transmission (PPTCT) of HIV AIDS program started in India in the year 2002. The aim of the PPTCT program is to offer HIV testing to every pregnant woman in the country so as to cover all estimated HIV positive pregnant women and eliminate transmission of HIV from mother to child.…”
Section: Introductionmentioning
confidence: 99%